Quality of evidence in the oral health international data: Contributions for a global profile - Sophia Queiroz Marques dos Santos; Angelo Giuseppe Roncalli da Costa Oliveira (PLoS ONE, 2025)
Introduction The Oral Health Country/Area Profile Project (CAPP) is the largest global database on oral health, compiling information from 205 countries, including 193 members of the World Health Organization (WHO). Although this database is a source of information and provides an overview of global oral health, the extent to which it accurately reflects oral health in specific countries is uncertain. Objective To analyze the quality of evidence underlying the global oral health profile provided by CAPP. Methods The Appraisal tool for Cross-Sectional Studies (AXIS) was adapted and used to assess data extracted from the methods section of included records. The results were then analyzed using the Item Response Theory (IRT) to establish the weightings of each dimension. The score was assessed in relation to variables of interest: age group, year of the record, and geographic region. Results The quality of oral health data showed polarization, with The quality of data from included documents varied according to age group analyzed, year of assessment, and geographic region. The Americas and Western Pacific regions demonstrated the highest quality of oral health data. Conclusion The global oral health profile depicted by CAPP may not accurately reflect reality. The process for including data in the database needs to be reviewed to ensure its reliability.